2011
DOI: 10.1088/0004-6256/141/5/156
|View full text |Cite
|
Sign up to set email alerts
|

SUBARU AND GEMINI HIGH SPATIAL RESOLUTION INFRARED 18 μm IMAGING OBSERVATIONS OF NEARBY LUMINOUS INFRARED GALAXIES

Abstract: We present the results of a ground-based, high spatial resolution infrared 18 µm imaging study of nearby luminous infrared galaxies (LIRGs), using the Subaru 8.2-m and Gemini South 8.1-m telescopes. The diffraction-limited images routinely achieved with these telescopes in the Q-band (17-23 µm) allow us to investigate the detailed spatial distribution of infrared emission in these LIRGs. We then investigate whether the emission surface brightnesses are modest, as observed in starbursts, or are so high that lum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
62
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 83 publications
17
62
1
Order By: Relevance
“…Ground-based imaging at 18 μm reveals a compact unresolved source (<120 pc) with high surface brightness and large Si optical depth (τ 18 = 0.7), in agreement with a buried AGN interpretation [20]. It is also worth noting that τ 9.7 can be combined with the EW of the 6.2 μm PAH feature in a diagnostic diagram that provides not only a direct classification but also possible indications on the evolutionary path of a source, by probing the age of the SB and the geometrical structure of the dust [21].…”
Section: Spitzer/irs Spectroscopysupporting
confidence: 73%
“…Ground-based imaging at 18 μm reveals a compact unresolved source (<120 pc) with high surface brightness and large Si optical depth (τ 18 = 0.7), in agreement with a buried AGN interpretation [20]. It is also worth noting that τ 9.7 can be combined with the EW of the 6.2 μm PAH feature in a diagnostic diagram that provides not only a direct classification but also possible indications on the evolutionary path of a source, by probing the age of the SB and the geometrical structure of the dust [21].…”
Section: Spitzer/irs Spectroscopysupporting
confidence: 73%
“…Only six Sy2 galaxies present extended MIR emission at large-scales (>400 pc, which is the sample average value) in the high angular resolution MIR data. These galaxies were previously studied in the MIR: a) NGC 4945 (Imanishi et al 2011 Here we make a comparison between this large-scale MIR emission as detected in the arcsecond and subarcsecond resolution data. In Fig.…”
Section: Kpc-scale Morphologiesmentioning
confidence: 98%
“…Díaz-Santos et al 2010, Díaz-Santos et al 2011, Imanishi et al 2011). Díaz-Santos et al (2010 found that, on average, the MIR continuum becomes more compact than the PAH emission as the MIR is increasingly dominated by the AGN.…”
Section: Parsec-scale Morphologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that AGN activity in Arp 187 might be already weaken and/or obscured. Infrared (IR) observations give us another secure way to find AGN since the AGN dust torus emission is dominated in mid-IR (Imanishi et al 2011;Ichikawa et al 2012Ichikawa et al , 2014Ichikawa et al , 2015. Utilizing the Spitzer mid-IR imaging data, Ohyama et al (2015) found AGN signs in the southern nucleus of NGC 3256 hosting molecule outflows (Sakamoto et al 2014).…”
Section: Introductionmentioning
confidence: 99%